Consumer Education and Traditional Foods: A Five-Year Review of Learning Experiences - Sudrajat, Ajat; Gaffar, Vanessa; Amanah, Dita; Krishna Yuliawati , Ayu; Monoarfa, Hilda; Sobandi, Ade; Lada, Suddin (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This study aims to explore consumer education experiences in choosing traditional foods as an essential component of the culinary industry, and to identify key factors influencing consumer preferences. Method: This research adopts a qualitative approach by examining consumer experiences through previous consumption, social interactions, sensory perceptions, and emotional connections with traditional foods. Data were analyzed to identify patterns in consumer decision-making processes, including demographic, cultural, and quality-related considerations. Results The findings reveal that consumer preferences for traditional foods are significantly influenced by prior experiences, social engagement, sensory attributes, special events, and emotional memories. In addition, demographic characteristics, food safety, perceived quality, and socio-cultural influences play important roles in shaping consumer choices. These factors collectively contribute to stronger consumer attachment and willingness to engage with traditional culinary products. Novelty: This study offers a comprehensive perspective by integrating consumer education experiences with emotional and cultural dimensions in the context of traditional foods. It highlights the importance of authentic and experience-based marketing strategies and provides insights into how technological advancements can be leveraged to enhance competitiveness in the traditional culinary industry.